1988
DOI: 10.1111/j.1365-2125.1988.tb05259.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lithium on the renal response to the dopamine prodrug gludopa in normal man.

Abstract: 1. The effect of oral lithium on the renal response to gamma‐L‐glutamyl‐ L‐dopa (gludopa, 25 micrograms kg‐1 min‐1) was investigated in seven normal males. 2. Gludopa at this dose produced an 800‐fold increase in urine dopamine excretion. It was natriuretic and suppressed plasma renin activity without altering blood pressure and pulse. 3. Lithium alone increased sodium excretion and stimulated plasma renin activity. However, it abolished the natriuresis produced by gludopa. 4. Gludopa did not significantly aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
2

Year Published

1989
1989
1996
1996

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 38 publications
1
16
2
Order By: Relevance
“…These results contrast with an earlier report by Jeffrey et al (1988) that lithium (in a higher dose of 750 mg) abolished the natriuretic response to the renal dopamine prodrug gludopa, suggesting that lithium interacts with dopamine at the proximal tubule. Girbes et al (1990) concluded that the interaction between lithium and the dopamine prodrug gludopa is not mediated by DA1-dopamine receptors or is confined to higher doses of lithium.…”
contrasting
confidence: 57%
See 2 more Smart Citations
“…These results contrast with an earlier report by Jeffrey et al (1988) that lithium (in a higher dose of 750 mg) abolished the natriuretic response to the renal dopamine prodrug gludopa, suggesting that lithium interacts with dopamine at the proximal tubule. Girbes et al (1990) concluded that the interaction between lithium and the dopamine prodrug gludopa is not mediated by DA1-dopamine receptors or is confined to higher doses of lithium.…”
contrasting
confidence: 57%
“…Furthermore, some caution with the interpretation of the results of Schoors & Dupont (1990) is required, because they did not find any natriuretic effect of lithium alone. This is in contrast with our results and those of Jeffrey et al (1988). Possibly there is a difference in salt status of the subjects studied at the beginning of the studies, which might influence the results.…”
contrasting
confidence: 56%
See 1 more Smart Citation
“…However, no significant changes occurred in this study with seven volunteers. In the study of Jeffrey et al (1988) Cavero et al (1987) demonstrated a rise of PRA by direct DA1 stimulation. The extent of increase in PRA during fenoldopam infusion was influenced by the presence of lithium and suggests that lithium enhances the effects of DA1-dopamine stimulation.…”
Section: Discussionmentioning
confidence: 78%
“…A recent publication (Jeffrey et al, 1988) suggests that lithium interacts with dopamine at the proximal tubule.…”
Section: Introductionmentioning
confidence: 99%